Efficient interactive multi-resolution rendering for translucent materials under area lights - Koa, Ming Di (2017)
Translucent materials exist all around us. They can be commonly found in materials such as marble, jade and fluids such as milk. Subsurface scattering describes one of the most complex yet beautiful effects of light in translucent materials. However, this light and media interaction is difficult to simulate. Although Monte Carlo approaches can simulate these effects, they are computationally expensive. Further complexities in simulation occur, when indirect illumination from translucent materials are considered, as they scatter light and illuminate other surfaces. In addition, when translucent materials are illuminated by area lights, fast techniques such as voxel based methods have difficulties in estimating direct visibility. In my research, I aim to develop efficient techniques for rendering homogeneous translucent materials under area light illumination at interactive speed.